Membangun Kesadaran Remaja Akan Dampak Pergaulan Bebas Terhadap Pembentukan Karakter - Lotulung, Mareike Sesca Diana; Kasingku, Juwinner Dedy (Peneliti.net, 2024)
Promiscuity among adolescents is becoming increasingly alarming today. Alcohol consumption, free sex, and other negative behaviors are openly practiced by teenagers. Teenagers, whose emotions are still fragile, and knowledge limited, are vulnerable to the influence of this social interaction, which ultimately can diminish their ability to advance society. With their crucial role as the nation's successors, teenagers have a responsibility to build a better future, characterized by forward-thinking and positive contributions to themselves, their families, and their communities. Therefore, special attention and concrete actions from various parties are greatly needed to prevent and cope the impact of promiscuity among teenagers. The research method used in this study is qualitative research with a literature review approach to explore the impact of promiscuity on the formation of teenage character and solutions that can be used to deter free association among teenagers. Character education holds the key to providing guidance and direction to teenagers, along with involvement from families, schools, and communities. With these efforts, it is hoped that a supportive environment for healthy teenage associations can be created, thus preventing harmful associations for teenagers and future generations